Ultrasound-derived tibia-fascia angle for noninvasive assessment of intracompartmental pressure in tibial plateau fractures - Heng Zhang; Luqi Li; Huiyang Jia; Haofei Wang; Qi Dong; Jialiang Guo; Heping Deng; Zhiyong Hou (PLoS ONE, 2026)
Background Current noninvasive diagnostics for acute compartment syndrome (ACS) lack clinical practicality and reliability. This study aimed to evaluate ultrasound-derived tibia-fascia angle (TFA) as a novel morphometric surrogate for intracompartmental pressure (ICP) assessment. Methods In this observational study, 105 patients with closed tibial plateau fractures were enrolled at a tertiary trauma center. TFA was bilaterally measured using B-mode ultrasound by blinded operators. Invasive ICP served as the reference standard. Correlations were analyzed via Spearman correlation analysis and multivariable linear regression, and diagnostic performance for high compartment pressure (HCP, ICP > 30 mmHg) was assessed using ROC analysis. Results ΔTFA showed a significant linear correlation with ICP after adjustment for confounders ( β = 1.74 mmHg/°, 95% CI: 1.07–2.41, P adj < 0.001) and a moderate monotonic association ( ρ = 0.545, 95%CI: 0.395–0.667, P < 0.001). For detecting HCP, ΔTFA achieved an area under the receiver operating characteristic curve (AUC) of 0.716 (95% CI: 0.621–0.812), with 86.5% sensitivity and 52.9% specificity at the optimal cutoff (ΔTFA ≥ 4.9°). Conclusion ΔTFA provides a rapid, operator-friendly method for noninvasive ICP estimation, demonstrating moderate diagnostic accuracy as a screening tool for HCP in tibial plateau fractures. Its integration into trauma workflows could enhance early risk stratification, particularly for high-energy fractures, though specificity limitations warrant complementary confirmatory tests.